Pengaruh Pemberian Minyak Jelantah 1,5 mL/Hari Selama 14 Hari Terhadap Histopatologi Hepar Rattus norvegicus Jantan - Ersa, Rakhmigasti Citra; Susianti, Susianti; Kurniawaty, Evi; Mustofa, Syazili (CV. Jasa Sukses Abadi, 2024)
Using cooking oil multiple times can caused bad effect on health one of them is liver damage. Free radical content in reused cooking oil trigger oxidative stress then disturb the cellular respons in liver. This study aimed to determine the effect of giving reused cooking oil for 14 days on rats (Rattus norvegicus) liver histopathology. This study was a true experimental using 10 rats (Rattus norvegicus) and were devided by 2 groups, which are normal group (KN) and treatment group (KP) that was given 1,5 mL reused cooking oil per day. After 14 days of treatment, rats were terminated and the liver were taken. To observe rats liver histopathology, cloudy swelling scoring were used on 5 field of view. Score 0: there was no cloudy swelling and necrosis found, score 1: there was 1-20% cloudy swelling and necrosis found, score 2: there was 21-50% cloudy swelling and necrosis found, score 3: there was 51-75% cloudy swelling and necrosis found, and score 4: there was more than 75% cloudy swelling and necrosis found.It was found a minimal cloudy swelling on KN with average liver damage score was 0,04. In group KP it were found cloudy swelling degeneration on all over the liver with average liver damage score was 4. Mann-Whitney test showed a significant difference between groups. Giving reused cooking oil 1,5 ml/day for 14 days caused damage on male rats liver histopathology.